KONTRIBUSI KOMUNIKASI INTERPERSONAL, KEPEMIMPINAN KEPALA SEKOLAH DAN BUDAYA KERJA ORGANISASI TERHADAP MOTIVASI KERJA DAN DAMPAKNYA PADA KEPUASAN KERJA GURU SMP N KECAMATAN WONOGIRI - Rahayu, Sri; , Prof. Dr. Sutama, M.Pd; , Dr. Suyatmini, M.Si (2016)
CONTRIBUTION OF COMMUNICATION INTERPERSONAL, LEADERSHIP PRINCIPAL AND CULTURAL ORGANIZATION WORKING ON WORK MOTIVATION AND ITS IMPACT ON TEACHER JOB SATISFACTION SMP N SUB WONOGIRI By: Sri Rahayu, Sutama and Suyatmini Graduate Student Education Administration Lecturer UMS srirahayu.1234@yahoo.com This study is a correlational study using a quantitative approach. In sampling the author uses simple random sampling technique with a number of teachers as the sample is as much as 182 teachers. Researchers in data collection using questionnaires. The results showed that: 1) Interpersonal communication has a positive and significant impact on work motivation; 2) Motivation have a impact no significant effect on work motivation; 3) Cultural organizations working have a impact no significant effect on work motivation; 4) Interpersonal communication has a positive effect but not significant to teacher job satisfaction; 5) Work motivation has a positive and significant impact on job satisfaction of teachers; 6) the organization's work culture has a positive and significant impact on job satisfaction of teachers; 7) Work motivation has a significant effect on job satisfaction but teachers; 8) Interpersonal communication and motivation to have simultaneous and significant influence on work motivation; 9) Work motivation and work culture organization does not have the effect of simultaneous and significant impact on work motivation; 10) Interpersonal communication and organizational work culture simultaneously influence and significant impact on work motivation; 11) Interpersonal communication, motivation and organizational work culture simultaneously influence and significant impact on work motivation; 12) Interpersonal communication and motivation to have simultaneous and significant influence on job satisfaction of teachers; 13) Work motivation and work culture of the organization has simultaneous and significant influence on job satisfaction of teachers; 14) Interpersonal communication and organizational work culture simultaneously influence and significant impact on job satisfaction of teachers; 15) Interpersonal communication, motivation and work culture of the organization has simultaneous and significant influence on job satisfaction of teachers; 16) Interpersonal communication, motivation and work culture of the organization directly affects work motivation; 17) Interpersonal communication, motivation and work culture of the organization directly affects job satisfaction of teachers. Keywords: interpersonal communication, school leadership, organizational work culture, work motivation, job satisfaction of teachers.